Possible immune mechanisms of gut microbiota and its metabolites in the occurrence and development of immune thrombocytopenia - Zhu, Gengda; Yan, Lixiang; Fang, Lijun; Fan, Chenyang; Sun, Hui; Zhou, Xinli; Zhang, Yucheng; Shi, Zhexin (Frontiers in Microbiology, 2024)
Immune thrombocytopenia (ITP) is an autoimmune disease characterized by increased platelet destruction and impaired production, leading to an elevated bleeding tendency. Recent studies have demonstrated an important link between the gut microbiota and the onset and progression of several immune diseases in humans, emphasizing that gut microbiota-derived metabolites play a nonnegligible role in autoimmune diseases. The gut microbiota and its metabolites, such as short-chain fatty acids, oxidized trimethylamine, tryptophan metabolites, secondary bile acids and lipopolysaccharides, can alter intestinal barrier permeability by modulating immune cell differentiation and cytokine secretion, which in turn affects the systemic immune function of the host. It is therefore reasonable to hypothesize that ecological dysregulation of the gut microbiota may be an entirely new factor in the triggering of ITP. This article reviews the potential immune-related mechanisms of the gut microbiota and representative metabolites in ITP, as well as the important influence of leaky gut on the development of ITP, with a view to enriching the theoretical system of ITP-related gut microecology and providing new ideas for the study of ITP.